Uncommon Female-Predominant Etiologies of Cryptogenic Stroke - Dong, Jing; Ma, Xin (Frontiers in Neurology, 2022)
The etiologies of cryptogenic stroke are complex and heterogeneous. A number of uncommon etiologies are not fully recognized, some of which predominantly affect female. Most of these etiologies are closely related to the hormonal level, reproductive factors, coagulation function and medications of female. Moreover, once cryptogenic stroke is diagnosed, female tend to have worse outcome. Therefore, prompt etiological recognition and treatment are crucial for good recovery. The aim of this article is to review advances in exploring uncommon female-predominant etiologies of cryptogenic stroke. These etiologies are categorized into arterial, cardiac and venous sources. Arterial vasoconstrictive narrowing, intimal injury and intimal developmental abnormality can cause brain ischemia or artery-to-artery cerebral embolism. Myocardial contraction dysfunction, cardiac wall injury and developmental abnormality can induce intracardiac thrombosis and lead to cardiac embolism. In addition, cortical venous thrombosis and occult venous thromboembolism via intracardiac or extracardiac channels also account for cryptogenic stroke in female. Due to the lack of knowledge, in clinical practice, the above etiologies were seldom assessed. The low incidence of these etiologies can lead to missed diagnosis. This review will provide novel clinical clues for the etiological diagnosis of cryptogenic stroke, and will help to improve the management and secondary prevention of stroke in the female population. In the future, more studies are needed to explore the etiology and prevention strategies of cryptogenic stroke.